Analisis Tingkat Kesejahteraan Keluarga Nelayan (Studi Kasus di Kelompok Nelayan “Tapang Kembar” Kelurahan Sanur, Kecamatan Denpasar Selatan) - SIWI, AVENTIA SELANIKA RIFANI; ANTARA, MADE; ANGGRENI, I.G.A.A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p03, 2023)
Analysis Welfare Level of Fishermen’s Families (Case Studies in the Fishing Group “Tapang Kembar” Sanur Village, South Denpasar District) Sanur is a popular local and international tourist destination with numerous small store and restaurants selling seafood. However, due to visiting limitations imposed during the pandemic, people's purchasing ability for catches and tourist attractions has been limited. This has a negative influence on the livelihoods of people, particularly the "Tapang Kembar" fishing community. This research was to know (1) Fisherman Income (2) The Level of Welfare of Fishermen’s Families (Case Studies in the Fishing Group “Tapang Kembar” Sanur Village, South Denpasar District). This research was carried out in a group of fishermen “tapang kembar” Sanur Village, South Denpasar District, location determination is done intentionally (purposive). The respondents in this study were 35 tradisional fishermen who used fishing rods and nets. For one year, a fisherman's family's income depends on fishing and no fishing revenue. The level of welfare of fishermen family is analyzed by criteria the central agency statistics 2018.The results showed that the income obtained by fishermen for one year was Rp 47.550.941. The income contributions of the fishing industry (on fishing) amount to 96,81% from the income of tradisional fisherman and contributions from businesses outside the fisheries sector is 3,18%. The monthly income of the fisherman's families in Sanur Village's "Tapang Kembar" fishing group is Rp 3.962.578. According to the criteria of the 2018 statistical center agency, there are 28 fishing families with a percentage of 80% belonging to prosperous families and seven fishing families with a percentage of 20% belonging to not prosperous families.